2021
DOI: 10.1089/lgbt.2020.0185
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Health-Related Quality of Life and Health Behaviors Among Lesbian, Bisexual, and Heterosexual Women Surviving Cancer from the 2013 to 2018 National Health Interview Survey

Abstract: Purpose: Health-related quality of life (HRQoL) and health behaviors contribute to cancer morbidity and mortality, which are elevated in lesbian and bisexual women (LBW). The purpose of this study was to assess differences in HRQoL and health behaviors between heterosexual and lesbian women and heterosexual and bisexual women cancer survivors. Methods: We pooled 2013-2018 National Health Interview Survey data. HRQoL comprised physical, mental, financial, and social health domains. Health behaviors included tob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 87 publications
(120 reference statements)
1
33
0
Order By: Relevance
“…Unmet needs included depression, sadness, cancer-related fears, uncertainty, stress, and sexual dysfunction [ 52 ]. Another study found bisexual women who had a history of cancer to be three times more likely to report psychological distress [ 97 ]. Bisexual individuals often experience dual discrimination by both mainstream and SGM communities, which may account for this heightened distress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unmet needs included depression, sadness, cancer-related fears, uncertainty, stress, and sexual dysfunction [ 52 ]. Another study found bisexual women who had a history of cancer to be three times more likely to report psychological distress [ 97 ]. Bisexual individuals often experience dual discrimination by both mainstream and SGM communities, which may account for this heightened distress.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations: No notable limitations. Hutchcraft et al (2020) [ 97 ] USA Lesbian and bisexual women who participated in the National Health Interview Survey 2013–2018 Quantitative Weighted, multivariable logistic regression was used to estimate odds ratios of heterosexual, lesbian, and bisexual women with a history of cancer on health-related QOL and health behaviors. With heterosexual women as the reference group, lesbian women were 58% more likely to self-report fair/poor health, almost twice as likely to report chronic obstructive pulmonary disease or heart conditions, and twice as likely to be current smokers; bisexual women reported three times the rate of psychological distress, twice the rate of heart conditions, nearly three times the rate of food insecurity, and were less likely to have a recent mammogram.…”
Section: Appendixmentioning
confidence: 99%
“…Growing evidence indicates that the incidence of COVID-19 is higher in communities of lower socioeconomic status, in which LGBTQ+ individuals are over-represented given their long history of economic marginalisation 48–51. Additionally, higher burdens of mental health and infectious diseases—due to the intersection of upstream determinants such as stigma, criminalisation of same-sex practices and sex work, and continued limited investment in these communities—place LGBTQ+ individuals at even higher risk 2 13 16. Such compounding vulnerabilities result in earlier disruptions to health services, leading to prolonged periods without access to care, especially during global crises 31.…”
Section: Discussionmentioning
confidence: 99%
“…Reports also indicate the unique concerns and challenges experienced by members of the LGBTQ+ community resulting from antigay backlash and community crackdown under false pretexts 12–14. Moreover, many members of the LGBTQ+ community are at increased risk for food insecurity, unemployment and unstable housing, thereby making them more vulnerable to the economic and health impacts from COVID-19 7 15–18…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence on psychosocial outcomes among this population of gynecologic cancer survivors is limited with inconsistent findings. 29 , 30 , 31 Given the potential impact of gynecologic cancer on psychosocial health outcomes in general, and the greater prevalence of clinical risk factors among sexual minority populations specifically, further identifying disparities among subgroups of survivors is necessary to identify highest risk individuals for worse outcomes. 32 , 33 We sought to compare self‐reported QOL and psychosocial measures between heterosexual and sexual minority gynecologic cancer survivors.…”
Section: Introductionmentioning
confidence: 99%